Seasonal dynamics of canine antibody response to Phlebotomus perniciosus saliva in an endemic area of Leishmania infantum - Velez, Rita; Spitzova, Tatiana; Domenech, Ester; Willen, Laura; Cairó, Jordi; Volf, Petr; Gállego, Montserrat (Parasites & vectors, 2018)
BACKGROUND: Canine leishmaniosis (CanL) is an important zoonotic parasitic disease, endemic in the Mediterranean basin. In this region, transmission of Leishmania infantum, the etiological agent of CanL, is through the bite of phlebotomine sand flies. Therefore, monitoring host-vector contact represents an important epidemiological tool, and could be used to assess the effectiveness of vector-control programmes in endemic areas. Previous studies have shown that canine antibodies against the saliva of phlebotomine sand flies are specific markers of exposure to Leishmania vectors. However, this method needs to be further validated in natural heterogeneous dog populations living in CanL endemic areas. METHODS: In this study, 176 dogs living in 12 different locations of an L. infantum endemic area in north-east Spain were followed for 14 months. Blood samples were taken at 5 pre-determined time points (February, August and October 2016; January and April 2017) to assess the canine humoral immune response to whole salivary gland homogenate (SGH) and to the single salivary 43 kDa yellow-related recombinant protein (rSP03B) of Phlebotomus perniciosus, a proven vector of L. infantum naturally present in this region. Simultaneously, in all dogs, L. infantum infection status was assessed by serology. The relationship between anti-SGH and anti-rSP03B antibodies with the sampling month, L. infantum infection and the location was tested by fitting multilevel linear regression models. RESULTS: The dynamics of canine anti-saliva IgG for both SGH and rSP03B followed the expected trends of P. perniciosus activity in the region. Statistically significant associations were detected for both salivary antigens between vector exposure and sampling month or dog seropositivity to L. infantum. The correlation between canine antibodies against SGH and rSP03B was moderate. CONCLUSIONS: Our results confirm the frequent presence of CanL vectors in the study area in Spain and support the applicability of SGH- and rSP03B-based ELISA tests to study canine exposure to P. perniciosus in L. infantum endemic areas.
Keywords: Markers of exposure; Immunity, Humoral; Endemic Diseases; Salivary Glands; roční období; Canine leishmaniosis; Saliva; Immunoglobulin G; sliny; imunoglobulin G; protilátky; leishmanióza; nemoci psů; Female; Longitudinal study; slinné proteiny a peptidy; Longitudinal Studies; Dog Diseases; North-east Spain; psi; Antibodies; hmyz - vektory; Leishmaniasis; endemické nemoci; slinné žlázy; Spain; Leishmania infantum; Saliva proteins; Salivary Proteins and Peptides; Seasons; Insect Vectors; zvířata; humorální imunita; ženské pohlaví; Španělsko; Dogs; Phlebotomus; Animals; longitudinální studie; protilátky protozoální; Phlebotomus perniciosus; Antibodies, Protozoan